The Efficacy of Eye Masks and Earplugs Interventions for Sleep Promotion in Critically Ill Patients: A Systematic Review and Meta-Analysis - Karimi, Leila; Rahimi-Bashar, Farshid; Mohammadi, Seyyede Momeneh; Mollahadi, Mohsen; Khosh-Fetrat, Masoum; Vahedian-Azimi, Amir; Ashtari, Sara (Frontiers in Psychiatry, 2021)
Using physical devices such as eye masks and earplugs to improve to the quality of sleep in intensive care units (ICUs) is a very important issue. This study was conducted to assess the efficacy of eye masks and earplugs for sleep promotion in critically ill adult patients in the ICU based on various sleep quality assessment tools. PubMed, Scopus, Web of Science, and ProQuest were systematically retrieved until May 2021. Both randomized and non-randomized experimental and quasi-experimental studies were included if they evaluated the efficacy of eye masks and earplugs interventions on sleep outcomes in critically ill patients. The methodological quality was assessed by the Joanna Briggs Institute (JBI) critical appraisal tool. For the main outcome (sleep quality), a mean difference (MD) and confidence intervals (CIs) of 95% were determined. A total of 2,687 participants from 35 studies met the inclusion criteria. Twenty one studies were included in meta-analysis and 14 studies were included in the qualitative analysis. According to the results based on sleep quality assessment tools; overall scores of Pittsburgh Sleep Quality Index (PSQI) and Richards-Campbell Sleep Questionnaire (RCSQ), eye mask and/or earplug interventions have a positive effect on sleep quality. Based on Verran-Snyder-Halpern Sleep Scale (VSHSS), sleep disturbance was significantly lower in the intervention groups. In terms of polysomnography, the use of eye masks and/or earplugs resulted in a significant increase in total sleep time, sleep efficiency, rapid eye movement (REM) time, significant reduction of awaking, and sleep arousals index. The results of the present study suggest that the use of earplugs or eye masks, separately or combined affects sleep improvement in critically ill patients